1997
DOI: 10.1002/(sici)1099-1441(199709)4:3<143::aid-kpm93>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Organizational change readiness practices of business turnaround change agents

Abstract: This paper summarizes the findings of an investigation of 145 business turnaround change agents (TCAs) to determine (a) the period of time expected to improve the performance of failing companies; (b) the extent of fear of job loss and resistance to change by managers in these companies; and (c) the readiness practices employed by TCAs in preparing managers for the organizational changes necessary to effect business turnarounds. These TCAs indicated that they expected to reverse a negative cash flow in 60 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 4 publications
0
25
0
2
Order By: Relevance
“…Employees using a strategy worldview construct meaning about why things are changing and thus "self-mitigate" the uncertainties that challenge commitment during change (Armenakis and Fredenberger 1997). This prediction is also consistent with previous research that has found that forming a strategic vision and sharing it with employees increases affective commitment through the ownership it creates among employees (Dvir et al 2004).…”
Section: The Role Of Psychological Resources In the Mcammentioning
confidence: 99%
See 1 more Smart Citation
“…Employees using a strategy worldview construct meaning about why things are changing and thus "self-mitigate" the uncertainties that challenge commitment during change (Armenakis and Fredenberger 1997). This prediction is also consistent with previous research that has found that forming a strategic vision and sharing it with employees increases affective commitment through the ownership it creates among employees (Dvir et al 2004).…”
Section: The Role Of Psychological Resources In the Mcammentioning
confidence: 99%
“…For example, scholars have examined how organizational members can adapt to change (e.g., Fugate et al 2002, Judge et al 1999, Kelman 2005, Self et al 2007, Smollan 2006 and are capable of being open to, or ready for, change (e.g., Armenakis and Fredenberger 1997, Herold et al 2007, Morrison and Phelps 1999, Wanberg and Banas 2000. To a large extent, this research focuses on a set of dispositional and contextual antecedents that can facilitate employee engagement with change, and not the interpretive variety in reactions to change.…”
Section: Introductionmentioning
confidence: 99%
“…American researchers Armenakis and Fredenberger (1997), considering the aspect of the development of adaptability and personnel readiness for changes, identified three strategies for successfully forming psychological readiness for changes:…”
Section: Resultsmentioning
confidence: 99%
“…Once the crisis‐as‐event model selects that focus, it engages in analysis of that event, asking questions including but not limited to: Is the event internal—say, a product failure resulting from a flawed product development process—or external—say, an environmental disturbance—to the unit? (Armenakis & Fredenberger, ). If the event is external, is its source political, social, economic, or natural? (Brockner & James, ; Falkheimer & Heide, ). Does the event pose a threat, an opportunity, or some combination of the two?…”
Section: Two Conceptual Model Of Crisismentioning
confidence: 99%